Peningkatan Keterampilan Laporan Keuangan Koperasi Berbasis Microsoft Excel di Koperasi Wanita Kenanga Madiun - Anisa Prima Dihastuti; Diyah Santi Hariyani; Vera Puspitasari; Adistya Amanda; Anggita Larentza; Oktavia Suryaningrum; Yovina Dwi Puspitasari; Muhamad Alika Nur Rohman (Kreativasi : Journal of Community Empowerment, 2023)
Koperasi Wanita Kenanga Madiun as a local economic entity, requires improved skills in preparing Microsoft Excel-based financial reports. These skills are important to ensure transparency, accuracy, and efficiency in cooperative financial management. Due to limitations, cooperative management still uses manual methods to record cooperative transactions. Besides, cooperative administrators also do not really understand the knowledge of financial reports using Microsoft Excel. Therefore, this service aims to improve Microsoft Excel-based Cooperative Financial Reports skills. This research uses a combination approach between lectures, questions and answers, and training methods followed by the management of the cooperative. After applying this method, there was a significant improvement in the skills of preparing financial statements using Microsoft Excel. Participants were able to effectively implement the concepts taught, increase efficiency in preparing financial statements, and reduce potential errors.